Kajian Brand Fashion Wanita Lokal Di Kota Bandung (Studi Kasus : Calla The Label dan Halona) - Mutiara Insani Nasution; Ira Wirasari; Arini Arumsari (Universitas Medan Area, 2022)
Fashion is a reflection of the self of its users. The existence of local women's fashion brands in the fashion industry is increasingly evident. One of the factors driving the success of a fashion brand is to use branding. However, the lack of knowledge of fashion brand owners regarding the importance of developing the right branding strategy for their company. In addition, how to increase the value of a brand by building brand awareness of potential consumers. This study aims to review the Calla The Label and Halona brands which then produce an adaptation of the branding strategy of the local fashion brand Calla The Label and then can be used and adapted by women's fashion brand owners in formulating branding strategies and developing their brands. The method used in this research is qualitative with literature study, interview, observation and data analysis. The review of these two fashion brands is expected to provide information regarding the use of branding strategies that are appropriate for beginners or those who are already established in the local fashion industry.